2021
DOI: 10.3390/nu14010159
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Dietary Intake from Grocery Shopping Data—A Comparative Validation of Relevant Indicators in Switzerland

Abstract: In light of the globally increasing prevalence of diet-related chronic diseases, new scalable and non-invasive dietary monitoring techniques are urgently needed. Automatically collected digital receipts from loyalty cards hereby promise to serve as an objective and automatically traceable digital marker for individual food choice behavior and do not require users to manually log individual meal items. With the introduction of the General Data Privacy Regulation in the European Union, millions of consumers gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…First, the FSA-NPS DI has been identified as a useful and validated tool to discriminate individuals according to the quality of the diet, allowing the monitoring of dietary change [49]. Second, within a comparative study among purchase quality indicators in Switzerland, the Nutri-Score framework has been validated to estimate diet activities from shopping data better than other purchase indicators [50]. Third, when compared to other front-of-package labels, the Nutri-Score label has been validated to show superior effectiveness among consumers, especially among the at-risk population [51].…”
Section: Futureme Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the FSA-NPS DI has been identified as a useful and validated tool to discriminate individuals according to the quality of the diet, allowing the monitoring of dietary change [49]. Second, within a comparative study among purchase quality indicators in Switzerland, the Nutri-Score framework has been validated to estimate diet activities from shopping data better than other purchase indicators [50]. Third, when compared to other front-of-package labels, the Nutri-Score label has been validated to show superior effectiveness among consumers, especially among the at-risk population [51].…”
Section: Futureme Interventionmentioning
confidence: 99%
“…Third, when compared to other front-of-package labels, the Nutri-Score label has been validated to show superior effectiveness among consumers, especially among the at-risk population [51]. Fourth, although the Nutri-Score framework was developed for rating individual products and not aggregated shopping baskets, its scoring mechanism has been proven to correlate with overall dietary behavior when applied on grocery purchase data sets [50].…”
Section: Futureme Interventionmentioning
confidence: 99%
“…Digital receipts from loyalty cards have a high potential as an automatic, self-updating, and scalable approach to provide automated insights into the nutrient profile of food products and development of personalized recommendations, especially in countries where loyalty card programs are widely used ( 56 58 ). In Switzerland, for example, the loyalty programs offered by Coop and Migros, the two main grocery stores, reach more than 3 million households each, and 80% of the retail revenues are associated to loyalty cards ( 59 , 60 ).…”
Section: Digital Solutions To Support Dietary Decision Makingmentioning
confidence: 99%
“…Examples include the Food Standards Agency Nutrient Profiling System Dietary Index (FSA-NPS DI) ( 64 ), the Healthy Trolley Index ( 65 ) or the Grocery Purchase Quality Index-2016 ( 66 ). A comparison between these food shopping quality indicators found that correlations between food shopping data and density-based relative food and nutrient intake are stronger than absolute food and nutrient intake ( 58 ). Unlike self-reported dietary intake, which assesses individual food intake, food items recorded with digital receipts are typically consumed by a whole household.…”
Section: Digital Solutions To Support Dietary Decision Makingmentioning
confidence: 99%
“…Given the increasing prevalence of diet-related chronic diseases, in the last paper of this Special Issue, Wu et al highlighted the need for the development of new scalable dietary monitoring techniques and presented the results of a study in Switzerland in which the nutritional quality of users’ diets was estimated based on digital receipts from grocery shopping [ 20 ].…”
mentioning
confidence: 99%